Combination of C21 and ARBs with rhACE2 as a therapeutic protocol: A new promising approach for treating ARDS in patients with coronavirus infection - Soheili, Marzieh (Med J Islam Repub Iran, 2020)
Background: Coronavirus disease 2019 (COVID-19) is caused by a new severe acute respiratory syndrome Coronavirus. COVID-19 patients are at risk for acute respiratory distress syndrome and death from respiratory failure. Methods: In this study the complete genome of the SARS-CoV-2 reference sequence, geologically isolated types, and Coronavirus related to human diseases were compared by the Molecular Phylogenetic Maximum Likelihood method. The secondary and tertiary structures of the main protease of SARS-CoV were defined as the most similar viruses to SARS-CoV-2, aligned with chimera software. Therefore, considering ineffective antiviral medications used for SARS-CoV and the importance of preventing acute respiratory distress syndrome as the main cause of mortality, 2 strategies were adopted to acquire the most effective drug combination. Results: The results of phylogenic analysis showed that SARS-CoV is the most similar virus to SARS-CoV-2. The secondary structure and superimposing of tertiary structure did not show a significant difference between SARS and SARS-CoV-2 3C-like main protease and the root means square deviation between Cα atoms did not support the difference between the 2 protein structures. Thus, these 2 mechanisms were fostered in accordance with the correlation between acute respiratory distress syndrome-related Coronavirus, angiotensin-converting enzyme 2 on one side and the possible treatments for reducing the respiratory side effects on the other. The analysis of renin-angiotensin system as well as the tested drugs applied to acute respiratory distress syndrome cases, indicated that angiotensin II receptor blockers, angiotensin-converting enzyme inhibitors, and C21 as nonpeptide agonist might possess a promising modality of treatment for acute respiratory distress syndrome. Furthermore, implementing recombinant human ACE2 as a competitive receptor might be an effective way to trap and chelate the SARS-CoV-2 particles. Conclusion: The data suggest that combination therapy of angiotensin II receptor blockers and C21 could be a potential pharmacologic regimen to control and reduce acute respiratory distress syndrome. Moreover, rhACE2 can be recommended as an effective protective antiviral therapy in the treatment of COVID-19 and its complications.